2005
DOI: 10.1021/bi0473206
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Bile Acid Hydrolase Is a Tetrameric N-Terminal Thiol Hydrolase with Specific Recognition of Its Cholyl but Not of Its Tauryl Product,

Abstract: Bacterial bile salt hydrolases catalyze the degradation of conjugated bile acids in the mammalian gut. The crystal structures of conjugated bile acid hydrolase (CBAH) from Clostridium perfringens as apoenzyme and in complex with taurodeoxycholate that was hydrolyzed to the reaction products taurine and deoxycholate are described here at 2.1 and 1.7 A resolution, respectively. The crystal structures reveal close relationship between CBAH and penicillin V acylase from Bacillus sphaericus. This similarity togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
176
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(182 citation statements)
references
References 51 publications
5
176
0
Order By: Relevance
“…It has been proposed, but not proven, that this broad enzyme activity is caused by the presence of free AC b-subunit. Limited homology of AC to conjugated bile acid hydrolase (CBAH) from Clostridium perfringens, with an available X-ray structure [35], has been used to generate homology structure models for AC [36,37]. These suggest that the a-subunit acts as a lid on the pocket.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed, but not proven, that this broad enzyme activity is caused by the presence of free AC b-subunit. Limited homology of AC to conjugated bile acid hydrolase (CBAH) from Clostridium perfringens, with an available X-ray structure [35], has been used to generate homology structure models for AC [36,37]. These suggest that the a-subunit acts as a lid on the pocket.…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation of the gene encoding CBAH-1 resulted in only partial reduction in BSH activity (BSH activity was 86% of that in the wild type), suggesting multiple BSH genes in C. perfringens. Furthermore, the crystal structure showed that the enzyme encoded by the CBAH-1 gene forms an active homotetramer (11). These observations, coupled with the detection of both intracellular and extracellular BSHs, provide further evidence for multiple isoforms, although the organization and regulation of the bsh gene(s) from C. perfringens are not known at present (22).…”
Section: Characteristics Of Bile Salt Hydrolase(s)mentioning
confidence: 96%
“…The conservation of tyrosine 82 (Tyr82) in penicillin V amidase and Asn82 in BSH are likely a result of differing steric requirements for their respective substrates (10). Recently, a bsh from Clostridium perfringens was crystallized both in the apoenzyme form and in complex with taurodeoxycholate (TDCA; hydrolyzed product) at resolutions of 2.1 and 1.7 Å , respectively (11). The structure revealed that the Cys2 residue is in position for nucleophilic attack of the Nacyl amide bond.…”
Section: Characteristics Of Bile Salt Hydrolase(s)mentioning
confidence: 99%
“…[9c, 11] NAAA has no sequence homology to FAAH, [9c] but is linked to the choloylglycine hydrolase family of enzymes, members of which are characterized by the ability to cleave carbon-nitrogen bonds in linear amides, with the exception of peptide bonds. [12] Like other Ntn enzymes, NAAA is produced as an inactive pro-enzyme and is activated at acidic pH by autocatalytic cleavage at a specific site of the peptide chain. [13] Site-directed mutagenesis experiments have univocally identified Cys131 (in mice) and Cys126 (in humans) as the catalytic residue responsible for both auto-proteolysis and FAE hydrolysis, [12,14] N-Acylethanolamine acid amidase (NAAA) is a cysteine amidase that preferentially hydrolyzes saturated or monounsaturated fatty acid ethanolamides (FAEs), such as palmitoylethanolamide (PEA) and oleoylethanolamide (OEA), which are endogenous agonists of nuclear peroxisome proliferator-activated receptora (PPAR-a).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Like other Ntn enzymes, NAAA is produced as an inactive pro-enzyme and is activated at acidic pH by autocatalytic cleavage at a specific site of the peptide chain. [13] Site-directed mutagenesis experiments have univocally identified Cys131 (in mice) and Cys126 (in humans) as the catalytic residue responsible for both auto-proteolysis and FAE hydrolysis, [12,14] N-Acylethanolamine acid amidase (NAAA) is a cysteine amidase that preferentially hydrolyzes saturated or monounsaturated fatty acid ethanolamides (FAEs), such as palmitoylethanolamide (PEA) and oleoylethanolamide (OEA), which are endogenous agonists of nuclear peroxisome proliferator-activated receptora (PPAR-a). Compounds that feature an a-amino-b-lactone ring have been identified as potent and selective NAAA inhibitors and have been shown to exert marked anti-inflammatory effects that are mediated through FAE-dependent activation of PPAR-a.…”
Section: Introductionmentioning
confidence: 99%